Design and Build Disaster Emergency Response Systems Using Firebase Cloud Messaging Based on Android and SMS Gateway - Tri Ferga Prasetyo; Rohmat Rohmat; Dadan Zalilluddin (Universitas Ahmad Dahlan, 2019)
Design and implementation emergency response system using firebase cloud messaging android based and sms gateway is a disaster notification information system using mobile android based media by utilizing support from firebase cloud message service and sms gateway. This study aims to assist BPBD Majalengka District in improving the effectiveness, accuracy, and speed of the process of delivering disaster information to the public. Applications use cross-platform messaging through firebase clouds that are able to perform real-time notification reporting to users with details or formatting of text, images, or map coordinates. This research uses Agile Method Development system with Rational Unified Process and software used in making this application is using Android Studio 2.3.2 and PHP programming language.